Religious Authority in Women’s Mosque (Ummul Mukminin Mosque at Universitas Islam Bandung): Otoritas Keagamaan di Masjid Perempuan (Masjid Ummul Mukminin di Universitas Islam Bandung) - Nur'aeni, Ulvah (Westscience Press, 2024)
This study spotlights women's religious authority in the Ummul Mukminin Mosque at Universitas Islam Bandung (Unisba). It seeks to investigate how female initiative negotiates with and coexists with existing (and generally male-dominated) religion, as well as the role of women in its re-emergence. In the early twentieth century, a new wave of women's revivalist groups promoted the role of women in public spaces such as mosques and madrasas, spreading new or reinvented forms of religious practice, attire, and interpretation among Muslim women. Furthermore, women with formal education gained access to employment prospects traditionally exclusive to men. Nonetheless, the growth of female religious roles presents both possibilities and barriers. Women's presence and involvement in the mosque are demarcated by general perceptions of women's prayer at home, gender stereotypes, and leadership restrictions on women. Therefore, this paper concerns the struggles of women in the academic community of Unisba to sustain their existence in a male-dominated public environment. According to the findings of this study, women's agency at Unisba elevates its religious authority through building the mosque and organizing the numerous religious events geared primarily at women's empowerment. The qualitative technique employed includes in-depth observation, interviews, and pertinent social media sources.